A Comparative Study on the Carbon Products from Hydrothermal Carbonization and Torrefaction Process Using Wood Fiber Waste - Noor Azlinna, Abu Bakar (2013)
Wood fiber waste is the one important biomass energy source to convert to value added product which is carbon particles. Hydrothermal carbonization (HTC) is the effective method to convert this biomass into carbon particles. The undesirable properties of biomass such as high moisture content and its heterogeneous nature pose a barrier to its competitiveness in the energy generation market. A best option to overcome the issues face with biomass is to carry out a pretreatment process called torrefaction. The physical characteristic of the carbon particles was determined by using FTIR, BET and FESEM. The main objectives of this study are to prepare carbon particles from hydrothermal carbonization and Torrefaction process using wood fiber waste and to identify physical characterization of carbon particle from the both processes. Proximate analysis has been done to identify the changes in chemical composition of the product. Based on the analysed, the product with higher energy density, low moisture content was produced from Torrefaction process. Torrefaction process produced lowest moisture content product which is about 3.99% to 4.47%. Ash content also shows that torrefaction process produced product with lowest percentage ash content compared to HTC and raw of wood fiber waste. The volatile matter left is from 53% to 91% for all the samples. Torrefaction also produce highest calorific value (24.894MJ/kg). FTIR analysis showed the hydroxyl, carbonyl, aliphatic, ethers, alcohol, phenol and carboxylic groups are present on the surface of the sample. Finally, it can be concluded that both processes is practicable method to convert biomass into value added product.